Armenia : Public Expenditure Review - World Bank (Washington, DC, 2013)
This is the first full scale World Bank Public Expenditure Review (PER) for Armenia. The primary objective of the Report was to review the main fiscal trends in Armenia for the period of 1997-2001 and develop recommendations with respect to further fiscal adjustment, expenditure prioritization, and budget consolidation. The report has the following structure. Chapter 1 reviews the main features of the Government's fiscal adjustment effort, initiated in the mid 90-s. It is focused on the analysis of aggregated indicators of fiscal performance such as deficit, public debt, budget arrears, and tax revenues. Chapter 2 looks at the main expenditure trends in the Armenia consolidated budget for 1997-2001 and makes an assessment of the quality and depth of expenditure restructuring undertaken in this period. Chapter 3 looks at the public sector's activities that remain non-reflected in the regular Government budget, which includes extra- budgetary funds, in-kind external grants, subsidies provided by the state-owned companies in the energy and utility sectors, and operations of the Social Insurance Fund. Chapter 4 presents in-depth analysis of progress made to date in the area of expenditure management and suggests a draft medium-term action plan to address identified weaknesses in budget preparation, presentation, execution, and reporting. Annexes 1 and 2 reflect more specific recommendations with respect to upgrading budget management procedures and the regulatory framework. Chapters 5-7 review expenditure policies in the main social sectors (health, education, social protection and insurance) and provide recommendations on: (i) how current expenditures could be made more efficient; (ii) what should be the main direction for intra-sectoral expenditure reallocation; and (iii) what should be medium-term targets for an increase in public expenditures in these sectors. Chapter 8 estimates a minimum level of budget support in core public infrastructure, which would stop deterioration of existing core assets in respective sectors and prevent the further accumulation of arrears. Sectoral Chapters 5-8 also provide recommendations for policy changes that would facilitate a return of these sectors to fiscal sustainability . Chapter 9 presents an analysis of Armenia's public investment program.